PERAN DINAS KESEHATAN KOTA PEKANBARU DALAM MEWUJUDKAN PUSKESMAS BERAKREDITASI DI KOTA PEKAN BARU TAHUN 2019 - Rachman Yoesuf Novrialdy; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Puskesmas accreditation is acknowledgment of puskesmass that is given by an independent institution that administers the accreditation stipukated by the Minister after it has been assessed that the puskesmas has met the health center service standards set by the Minister to improve the quality of puskesmas services on an ongoing basis. All of the puskesmas in Pekanbaru City have received accreditation, but none of the puskesmas have received complete accreditation, which is the highest accreditation.The purpose of this study is to determine the role of the Pekanbaru City Health Office in realizing an accredited health center in Pekanbaru City in 2019 and its inshibiting factors the role of the Pekanbaru City Health Office in realizing an accredited health center in Pekanbaru City in 2019. This study uses a qualitative approach with descriptive method. In collecting data, the writer used interview and documentation techniques.The results of this study found that the role of the Pekanbaru City Health Office in realizing accredited health centers in Pekanbaru City in 2019 has not been carried out optimally, there are still problems found in the field due to several factors, both from internal such as alack of budget then external factors such as the number of employees. Puskesmas that do not yet understand what puskesmas accreditation is, so implementation of puskesmas accreditation activities in Pekanbaru City has not been maximized.Keywords : Puskesmas Accreditation, Planning, organization, Actuating, supervision.